Efektifitas Manajemen Sumber Daya Manusia Melalui Pelatihan dan Konseling pada Komunitas Mahasiswa Luwuk, Kabupaten Banggai Provinsi Sulawesi Tengah - Kasmayani, Kasmayani; Lambause, Awaldin; Lambause, Hasan (Universitas Syiah Kuala, 2025)
The training and counseling program for optimizing human resource management in the Luwuk city community organization, banggai, aims to overcome challenges in human resource management which often hinder organizational effectiveness. This program is designed to improve managerial skills, provide psychosocial support, and strengthen networks between communities. The methodology applied includes training workshops, counseling sessions, mentoring programs, and discussion forums. Training covers aspects of effective communication, leadership, conflict management, and strategic planning, while counseling sessions focus on personal and professional development. Mentoring and coaching programs are implemented to facilitate the transfer of knowledge and experience. The discussion forum aims to share knowledge and best practices between community members. The expected impact of this program is increasing human resource management capacity, member welfare, forming a stronger network, and developing future leadership. The program presents a holistic approach that prioritizes not only skills development but also emotional and psychosocial support, which is essential for the sustainability and growth of the community in Luwuk. In conclusion, this program aims to create a significant positive impact on community organizations in Luwuk, through improving the managerial skills and welfare of community members.